Towards a framework of relationship marketing : a case study approach - Peck, H. L. (Cranfield University, 2000)
For almost half a century, academics have laboured over the refinement of managerial models of marketing derived, originally, from studies of consumer goods marketing in North America. These models were firmly rooted in the microeconomic market model and ideas of monopolistic competition. Yet critics have long argued that these managerial models and the assumptions on which they were based were inappropriate for international, business-to business or services marketing situations. From the mid-1980s onwards, alternative approaches to marketing theory began to emerge, in response to a widening gap between classical marketing theory and marketing practice. These alternatives were loosely grouped together under the umbrella of 'relationship marketing'. As interest in relationship marketing increased, so did demands for the development of new frameworks that conceptualised its scope and properties. Given the apparent absence of such frameworks, this research set out to contribute to knowledge through the development of a broad-based empirically grounded framework of relationship marketing. Three case studies were undertaken in pursuit of this objective. In each instance the focal firms studied were UK-based manufacturers of branded consumer goods, who marketed their products around the globe. Although all were manufacturers of consumer products, in each instance there were vital business-to-business marketing and service issues involved. In constructing an empirically grounded framework of relationship marketing, at the level of the organisation set, this research bridges a well-documented gap in the literature. It links the large body of managerially focused work on relationship marketing to that by academics pursuing the study of markets-as net works. However, the alleged difficulties associated with the execution of methodologically sound case-based research are also well documented. Consequently, this research sought to contribute to the development of case based research methods by introducing the use of experienced practitioners as independent 'expert validators' to verify critical stages of the case analysis.